2021
DOI: 10.21873/anticanres.14928
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Water-to-total Body Water Ratio as an Objective Biomarker for Frailty in Lung Cancer Patients

Abstract: Background/Aim: Our previous study revealed the association between extracellular water-to-total body water ratio (ECW/TBW) and the therapeutic durability of chemotherapy and/or immune checkpoint inhibitors in advanced lung cancer. We retrospectively examined the usefulness of ECW/TBW in detecting frailty compared to other bioelectrical impedance (BIA) parameters in a larger number of patients. Patients and Methods: Lung cancer patients underwent BIA before anti-cancer therapy at our hospital between June 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have indicated that a high ECW/TBW was related to the volume of cancer 17 and poorer tolerance to cancer therapies 18 and induced postoperative complications in esophageal, 19 head and neck, 20 and lung cancers. 21 Moreover, poor prognoses in patients with metastatic cancers are known. 10 Furthermore, several reports have indicated that ECW/TBW, compared with other BIA parameters, such as muscle and fat mass, more accurately detects frailty, suggests that a high ECW/TBW might subsequently cause cachexia leading to sarcopenia and frailty in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that a high ECW/TBW was related to the volume of cancer 17 and poorer tolerance to cancer therapies 18 and induced postoperative complications in esophageal, 19 head and neck, 20 and lung cancers. 21 Moreover, poor prognoses in patients with metastatic cancers are known. 10 Furthermore, several reports have indicated that ECW/TBW, compared with other BIA parameters, such as muscle and fat mass, more accurately detects frailty, suggests that a high ECW/TBW might subsequently cause cachexia leading to sarcopenia and frailty in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulating evidence has shown that sarcopenia and frailty can be induced by various mechanisms, such as malnutrition, systemic inflammation, and other organ diseases. Previous studies have indicated that a high ECW/TBW was related to the volume of cancer 17 and poorer tolerance to cancer therapies 18 and induced postoperative complications in esophageal, 19 head and neck, 20 and lung cancers 21 . Moreover, poor prognoses in patients with metastatic cancers are known 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies related to early increases in extracellular water ratio in tumor patients lacking signs of edema have not been reported, and the clinical in uences are not clear. Recent studies have shown that increased extracellular water ratio is a risk factor for disease progression, recurrence and long-term survival [6][7], and can mediate early death in tumor patients through other factors [8]. This suggests that early attention and early intervention of edema can help to reduce adverse effects and improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hirashima and Noda et al. ( 11 ) reported that a high extracellular water (ECW)/total body water (TBW) ratio was associated with frailty and poor treatment tolerance in patients with lung cancer ( 11 , 12 ). Due to the high water content of the human skeletal muscle, ICW is closely related to muscle mass.…”
Section: Introductionmentioning
confidence: 99%